Enzymatic protein hydrolysates of a residue from grape by-products industry for winemaking application: influence of the starting material and hydrolysis time - Ana Belén Mora-Garrido; M. Luisa Escudero-Gilete; Francisco J. Heredia; María Jesús Cejudo-Bastante (Cogent Food & Agriculture)
Large quantities of defatted grape seed meal (DGSM) are discarded annually in the grape pomace industry. This residue could be exploited as a new source of non-animal protein to improve the chemical and color stabilization of red wines from warm regions. Different protein hydrolysates have been characterized, considering two different variables in their obtaining: type of raw material (DGSM from white and red grape pomaces) and hydrolysis time (1 and 4 h). The protein content of the hydrolysates, their molecular weight distribution, color, amino acid and peptide composition, and antioxidant activity were evaluated. Products obtained were mainly influenced by the type of raw material, regardless of the hydrolysis time. Hydrolysates from red DGSM displayed a higher protein content (∼67.4%) and protein yield (∼28.9%), visually perceptible (ΔE*ab > 3) lower lightness (∼23.3) and color intensity (∼13.2), and a greater variety of peptides related to red wine color stabilization. However, hydrolysates from white DGSM showed a higher amino acid content and antioxidant capacity (∼33.5 µmol TE/g, by DPPH; ∼3710.9 µmol TE/g, by ORAC). According to the results obtained, both red and white DGSM are susceptible starting materials to be selected as optimal for application in winemaking, fixing 1 h as hydrolysis time.